Regorafenib in Glioblastoma Recurrence: How to Deal With MR Imaging Treatments Changes - Gaudino, Simona; Marziali, Giammaria; Giordano, Carolina; Gigli, Riccardo; Varcasia, Giuseppe; Magnani, Francesca; Chiesa, Silvia; Balducci, Mario; Costantini, Alessandro Maria; Della Pepa, Giuseppe Maria; Olivi, Alessandro; Russo, Rosellina; et al. (Frontiers in Radiology, 2022)
The treatment of recurrent high-grade gliomas remains a major challenge of daily neuro-oncology practice, and imaging findings of new therapies may be challenging. Regorafenib is a multi-kinase inhibitor that has recently been introduced into clinical practice to treat recurrent glioblastoma, bringing with it a novel panel of MRI imaging findings. On the basis of the few data in the literature and on our personal experience, we have identified the main MRI changes during regorafenib therapy, and then, we defined two different patterns, trying to create a simple summary line of the main changes of pathological tissue during therapy. We named these patterns, respectively, pattern A (less frequent, similar to classical progression disease) and pattern B (more frequent, with decreased diffusivity and decrease contrast-enhancement). We have also reported MR changes concerning signal intensity on T1-weighted and T2-weighted images, SWI, and perfusion imaging, derived from the literature (small series or case reports) and from our clinical experience. The clinical implication of these imaging modifications remains to be defined, taking into account that we are still at the dawn in the evaluation of such imaging modifications.